PENGARUG ASI EKSKLUSIF TERHADAP HIPERBILIRUBINEMIA NEONATUS : Literature Review - Lilis Sari (2020)
Exclusive breastfeeding is given to newborns until the age of 6 months. Breast milk is one of the primary precautions given to infants to treat hyperbilirubinemia. Breast milk can reduce the high risk of hyperbilirubinemia. the purpose of this research is to analyze the effect of exclusive breastfeeding on neonatal hyperbilirubinemia. This research uses the literature review method by using a database through Google Scholar, Pubmed, Sage Journal. The results of the study show that 9 research articles were obtained in 2015 to 2020. The number of samples examined from each article or thesis was 55 to 634 samples and all of them used primary data. Most of the research designs used Quasi experiment 3 articles, khort 1 articles, descriptive 2 articles and cross sectional 3 articles. The conclusion is exclusive breastfeeding in infants affects a decrease in hyperbilirubin levels. With frequency of administration as often as mukin 8 to 12 times per day can significantly reduce hyperbilirubin. Suggestions for nursing education can develop research on the importance of breastfeeding health education for babies with jaundice or hyperbilitubin. Keyword: exclusive breastfeeding, hyperbilirubinemia newborns,literature review